PENDUGAAN HERITABILITAS KETAHANAN BEBERAPA VARIETAS KENTANG (Solanum tuberosum L) TERHADAP LALAT PENGOROK DAUN (Liriomyza huidobrensis) - Boedi Santoso (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Cultivated potato (Solanum tuberosum) is an economically important crop world wide as shown by its increasing demand each year.  However, the relatively high demand of this crop is hard to meet due to leaf miner flies (Liriomyza huidobrensis) attack which could reduce potato production up to 70 percent.  The devastation is due to the ability of the flies’ imago to suck up leaf liquid and then lay their eggs which in turn develop into larvae which fed on the potato leaves.  To overcome this problem, it was necessary to assess the heritability resistance of some potato varieties to leafminer flies.  Therefore, the aim of the present study was to identify some parameters genetically resistance to leafminer flies on the potato plant. The study took place in Ngadas Village, Sukapura District of Probolinggo Residence from June to August 2007.  L  huidobrensis flies and six potato varieties such as Granola, Granola Kembang, Granola Lembang, HK, Atlantik, and Sulur were used.  The study results showed that trichome density of lower (73.29%) and upper (67.76%) leaves had high resistance heritability assessment. Such parameters with high heritability assessment can be used as selection criteria for plant breeding program.